Failure analysis of pulverizer pipe elbow in PLTU boiler - Hendri Chandra; Rizki Zulkarnain; Muhammad Rafli Fazal (Calamity: A Journal of Disaster Technology and Engineering, 2023)
Erosion occurs due to several different mechanisms, depending on the composition, size, shape of the eroding particles, speed, angle of impact, and surface composition of the eroded components. The pulverizer pipe elbow has become worn out due to the pulverized coal fluid abrasion flowing on the pipe, which the type is AISI Grade 1026. This study was carried out on the causes of this damage case. Damage to the elbow in the boiler needs to be analyzed for the failure of the elbow so that the damage's cause is known and it becomes a lesson so that the same damage does not occur again. The research aims to: 1. Find out the cause of damage to the pulverizer elbow on the boiler; 2. Know the correct maintenance strategy to increase the reliability of pulverizer pipes in boilers; 3. Simulate erosion due to coal particles in the pulverizer pipe using the Autodesk Simulation Computational Fluid Dynamics software program; 4. Analytical calculations of the erosion rate that occurs at the bend of the pulverizer pipe (elbow) in the boiler. The analysis was done by visual observation, hardness testing, metallographic observation, simulation of the ANSYS CFD program, and analytical calculation. The result of the ANSYS simulation showed that the main factor causing the leakage was erosion-corrosion. In the leaking area, the corrosion concentration was higher than in other areas, indicated by the red color in that area. From the calculation results, it was concluded that the largest erosion rate occurs at the angle of 200 with the value is 4.9548 x 10- 11 m3 / s, the smaller the pulverized coal’s angle of impact crashed the pulverizer pipe elbow, the greater the erosion.